Environmental DNA metabarcoding for whole community inventories of vertebrates in rivers of the midwestern United States - Sophie Picq; Amanda N. Curtis; Andrew George; Eric R. Larson; Michelle E. Thompson; Philip W. Willink; Caleb D. McMahan; Lesley S. de Souza (Journal of Freshwater Ecology)
The application of environmental DNA (eDNA) methods to simultaneously study vertebrate diversity holds promise to accelerate conservation efforts, especially in freshwater systems which are among the most imperiled in the world. Here, using eDNA sampling, we identify patterns of vertebrate biodiversity across different habitats of the Kankakee River watershed, one of the most diverse lotic systems in Illinois, USA. Our eDNA metabarcoding analyses identified 147 different taxa, including 77 fishes, 38 birds, 24 mammals, five amphibians and three reptiles at 11 locations in the watershed, including tributaries and mainstem stretches upstream and within the Kankakee River State Park protected area. When compared to seining, eDNA sampling consistently detected more fish species, including non-native and imperiled species. We also found that vertebrate communities among the different habitats significantly varied in taxonomic composition, showing an upstream-downstream shift along the mainstem river as well as tributary-specific assemblages. Our study demonstrates the ability of single-marker eDNA metabarcoding to simultaneously document aquatic and terrestrial communities across large temperate lotic ecosystems and to monitor diversity patterns across protected areas.